The Blockade of Store-Operated Calcium Channels Improves Decompression Sickness in Rats - Tang, Shih-En; Liao, Wen-I; Wu, Shu-Yu; Pao, Hsin-Ping; Huang, Kun-Lun; Chu, Shi-Jye (Frontiers in Physiology, 2020)
Background: Previous investigations reveal that BTP2, a store-operated calcium channel blocker, has protective and anti-inflammatory properties in multiple inflammatory diseases. This study investigates whether BTP2 can protect against decompression sickness (DCS) in a rat model. Methods: BTP2 (2 mg/kg) was administered to male Sprague Dawley rats 30 min before subjecting them to hyperbaric pressure. Control rats were not treated. After decompression, signs of DCS were examined, and samples of bronchoalveolar lavage fluid (BALF) and lung tissue were obtained for evaluation. Results: The incidence and mortality of DCS were decreased significantly in rats treated with BTP2 compared to those treated with dimethyl sulfoxide. BTP2 significantly attenuated DCS-induced lung edema, histological evidence of lung inflammation, necroptosis, and apoptosis , while it decreased levels of TNF-alpha, IL-6 and CINC-1 in BALF. Additionally, BTP2 reduced the expression of nuclear factor of activated T-cells and early growth response protein 3 in lung tissue. BTP2 also significantly increased the levels of IkappaB-alpha and suppressed the levels of nuclear NF-kappaB in lung tissue. Conclusions: The results suggest that BTP2 may has potential as a prophylactic therapy to attenuate DCS-induced injury.